The Ecotourism Village: ENVIRONMENTALLY BASED TOURISM AREA DEVELOPMENT PLANNING IN IMPROVING THE COMMUNITY ECONOMY - Sri Rahayu Ayuba; Dewi Sartika T. Zees; Bambang Djau (JURNAL ABDIMAS DOSMA (JAD), 2024)
The Pontolo Atas the village in North Gorontalo, Indonesia, is participating in a community engagement initiative focused at fostering sustainable tourism. The research problem addressed is the need to improve the local community's economic well-being through the development of eco-tourism. Participatory dialogue seminars with the local community are part of the program to promote awareness about the necessity of environmental conservation and the possibility for eco-tourism development. The process includes engaging with the local community and government officials to educate them on eco-tourism management and social media marketing strategies. The findings imply an increase in community awareness and knowledge of eco-tourism, which could contribute to economic growth. The program's consequences include the possibility for long-term economic development and environmental conservation.